Activation of central melanocortin pathways by fenfluramine - Heisler, Lora K. (2002)
D-fenfluramine (d-FEN) was once widely prescribed and was among the most effective weight loss drugs, but was withdrawn from clinical use because of reports of cardiac complications in a subset of patients. Discerning the neurobiology underlying the anorexic action of d-FEN may facilitate the development of new drugs to prevent and treat obesity. Through a combination of functional neuroanatomy, feeding and electrophysiology studies in rodents, we show that d-FEN-induced anorexia requires activation of central nervous system melanocortin pathways. These results provide a mechanistic explanation of d-FEN's anorexic actions and indicate that drugs targeting these downstream melanocortin pathways may prove to be effective and more selective antiobesity treatments.